Surgical anatomy and clinical variation of the left colonic artery in laparoscopic anterior rectal resection - Li, Jiajun; Zhao, Xiaofang; Yi, Bo; Fu, Chuanchuan; Xu, Peipei; Chen, Chao; Zhao, Bin; Zheng, Yangchun (Frontiers in Surgery, 2024)
Objectives To investigate the surgical anatomy and clinical variation of the left colonic artery (LCA) during laparoscopic anterior rectal resection. Methods We retrospectively analysed 87 colorectal cancer patients who underwent laparoscopic anterior rectal resection with preserved LCA at the Department of Gastroenterology, Sichuan Cancer Hospital from March 2018 to April 2022, aiming to observe the emanation location, anatomical typing, and travel trajectory of the LCA as well as its relationship with the inferior mesenteric vein (IMV). Results From all cases, we observed that the LCA emanated from the left side of the inferior mesenteric artery (IMA), and the average distance was approximately (3.5±1.1) cm from the root of the IMA to the emanation of the LCA; specifically, 35 of these cases had the LCA branching from the IMA alone (type I, 40.2%);16 cases had the LCA cotruncating with the sigmoid artery (SA) (type II, 18.4%), 30 cases had the LCA cotruncating with the superior rectal artery (SRA) and SA (type III, 34.5%), and 6 cases had the LCA cotruncating with four or more branches of the SRA and SA (type IV, 6.9%). No LCA agenesis cases were found in this group. In addition, we also observed LCA alignment: 25 LCA cases crossed the IMV diagonally upwards (type A, 28.7%); 36 cases of LCA crossed the IMV arching upwards (type B, 41.4%); 18 cases of LCA crossed the IMV vertically outwards (type C, 20.7%); and 8 cases of LCA crossed the IMV diagonally downwards (type D, 9.2%) .Among them, 2 cases developed anastomotic fistula, one case had chyle leakage one week after surgery, and 4 cases experienced urinary retention; all of them recovered and were discharged after conservative treatment. Conclusion The anatomy and variation of the LCA can be observed clearly and accurately during laparoscopic surgery. Understanding the type and variation of the LCA helps to dissect the vessels in the IMA region during surgery, especially in operations where the LCA is preserved, and reduce the incidence of vascular injury and its complications.